Manajemen Pendidikan Inklusi di Sekolah Dasar - Lestari, Atun; Setiawan, Farid; Agustin, Eviana (Lembaga Yasin AlSys, 2022)
Knowing how the management or management of inclusive education in elementary schools is the goal of this research. Inclusive education that has been implemented in Indonesia has many problems, these problems include principal policies, teacher-student relations, and it is often found that educators lack the ability to run inclusive programs. In this case the educator is the most important part of a school institution for the smooth running of the previously agreed upon program, because educators will communicate directly with normal students and students with special needs. The understanding, knowledge, experience and skills of an educator determine how good and well an inclusive program is manifested in inclusive schools, especially in the classroom. To make this happen, educators are required to attend several trainings to accommodate and carry out agendas or plans properly.